2014
DOI: 10.1007/s13197-014-1668-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of pulsed electric field in the production of juice and extraction of bioactive compounds from blueberry fruits and their by-products

Abstract: The influence of Pulsed Electric Field (PEF) pretreatment of blueberry fruits (Vaccinium myrtillus L.), both on the extraction yield and antioxidant properties of juice obtained by pressing and on the on the recovery of bioactive compounds from berry by-products (press cake) by extraction with solvent, was investigated. PEF treatments carried out at field strengths of 1, 3, and 5 kV/cm and an energy input of 10 kJ/kg achieved a cell disintegration index (Z p ) of 0.70, 0.80, and 0.87, respectively. Mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(92 citation statements)
references
References 28 publications
8
81
0
3
Order By: Relevance
“…Celli et al, (2014) reported a range from 7.57 to 113 mol/g FW of FRAP values in different berries, which was quite similar to our results. Bobinaitė et al (2014) reported that FRAP capacity in blueberry juice varied from 5 to 7 mol/ml, which was quite similar to our results. Borges et al (2010) found that anthocyanins had the highest influence on the antioxidant capacity, followed by flavanols and flavonols.…”
Section: Polyphenolic Concentrations In Dried Pomaces and Cranberry Jsupporting
confidence: 92%
“…Celli et al, (2014) reported a range from 7.57 to 113 mol/g FW of FRAP values in different berries, which was quite similar to our results. Bobinaitė et al (2014) reported that FRAP capacity in blueberry juice varied from 5 to 7 mol/ml, which was quite similar to our results. Borges et al (2010) found that anthocyanins had the highest influence on the antioxidant capacity, followed by flavanols and flavonols.…”
Section: Polyphenolic Concentrations In Dried Pomaces and Cranberry Jsupporting
confidence: 92%
“…higher electric field strength applied did not further enhance the extraction of phenolic compounds from sour cherry by-products (Table 2). Interestingly, in our previous work, the extractability of phenolic compounds from blueberry by-products was shown to be dependent on the applied electric field strength (Bobinaitė et al, 2015). As it was previously documented, the influence of PEF treatment on extractability of phenolic compounds depends on the location of these compounds in the plant cell and also on the cell size distribution between berry skin and flesh (Corrales et al, 2008;Barba et al, 2015).…”
Section: Resultsmentioning
confidence: 64%
“…Thus, performed experiment indicates that there are some optimal conditions for the electroporation to proceed. What more, in some publications we can see that the electric field intensity plays a role even more important role than specific energy input (Bobinaitė et al, 2015;Toepfl & Heinz, 2011). However, such statement should be rather considered as an assumption and it requires more research in order to make a general conclusions.…”
Section: Pulsed Electric Field Treatment Efficiency Assessmentmentioning
confidence: 97%